Analisis Lalu Lintas Terhadap Kapasitas Jalan Jolotundo Kota Semarang - Wardani, Agustina; Ilonka, Willy Anastasya (Center for Environmental Research, LPPM, Universitas Sebelas Maret, 2022)
Road capacity is the ability of road sections to accommodate ideal traffic flow or volume in a certain unit of time, expressed in the number of vehicles passing through a certain road section in one hour. The purpose of this study is to determine the performance of road traffic by calculating passing vehicles, road geometric conditions and environmental conditions. The study conducted in this research is conducted on the Jolotundo road section of Semarang city with the aim of calculating capacity and level of service, namely by conducting surveys (starting from 06.00 - 09.00 and 15.00 - 18.00), the data obtained are traffic volume data, vehicle speed and road geometric data. The data processing was carried out using the 1997 Indonesian Road Capacity Manual (MKJI) method where the degree of saturation (DS) as an indicator of traffic behavior on the Jolotundo section of Semarang City. From the results of the survey data processing, the capacity value on this road section is 1543.25 smp/hour and the level of service at LOS C with a value of 0.49, which means that the traffic volume on the Jolotundo road section currently has a stable flow, but the speed and movement of vehicles are controlled.